Daily skin care habits and risk of rosacea - Li MA; Bin WANG; Suchun HOU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2021)
Objective: To investigate the association between the daily skin care habits and the risk of rosacea. Methods: A questionnaire survey on daily skin cares was conducted among rosacea and non-rosacea patients in our clinics. Gender, age, daily skin care procedures were assessed, and the chi-square test was used to analyze the difference between rosacea and non-rosacea patients. The logistic regression was used to analyze the independent risk factors for rosacea. Results: 487 valid questionnaires were collected. 144 rosacea patients had been identified among the respondents. The results of univariate analysis showed that there were significant difference between rosacea and non-rosacea patients (all P<0.05). Logistic regression analysis showed that female (OR=4.46, P<0.01), daily usage of mask (OR=1.99, P=0.04) and daily usage of acid cosmetics (OR=11.39, P=0.04) were independent risk factors for rosacea. Conclusion: Inappropriate daily skin care can increase the risk of rosacea.